Phishing website detection - Nur Sholihah, Zaini (2018)
The Internet has become an integral part of our daily social and financial activities. The Internet is important not only for individual users, but also for organizations, as organizations that offer online commerce can gain a competitive advantage by serving global customers. The Internet makes it possible to reach customers all over the world without market restrictions and with effective e- commerce. As a result, the number of customers using the Internet to make their purchases is increasing significantly. Hundreds of millions of dollars are transferred every day over the internet. This amount of money tempted the fraudsters to carry out their illegal activities. Therefore, Internet users may be vulnerable to various types of web threats that may cause financial harm, credit card fraud, loss of personal data, potential damage to brand reputation, loss of trust in e - commerce and online banking by customers. Hence, the suitability of the internet for commercial transactions is questionable. Phishing is considered a form of web threats that is defined as the art of impersonating a legit website to obtain usernames, passwords and credit card details. In this study, the phishing phenomena will be discussed in detail. In addition, we present a study on the state of research on the topic. Furthermore, we aim to identify the current developments in phishing and its precautionary measures, and to conduct a comprehensive study and evaluation of this research to close the gap that still exists in this area. This research focuses primarily on web - based phishing detection methods, not email - based detection methods.